2020
DOI: 10.1021/acs.jafc.0c04171
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Potential of Bordeaux Grape Cultivars: Identification and Assays on 4-Oxononanoic Acid, a γ-Nonalactone Precursor

Abstract: γ-Nonalactone has been demonstrated to be a chemical marker of dried/cooked fruit nuances detected in must and wine, but little is known about its formation pathways. Therefore, on the basis of the literature, we hypothesized 4-oxononanoic acid as a potential precursor. Using dichloromethane extraction followed by gas chromatography coupled to negative chemical ionization mass spectrometry, this keto acid was identified and quantified in Merlot and Cabernet Sauvignon musts. Its concentration ranged from traces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The lifecycle of the most common fungal diseases is well-characterized, as is their negative impact on grapevine physiology; yet, for most diseases, the molecular mechanisms that underpin the deterioration of berry quality remain to be elucidated. Recent advances in metabolomics led to the discovery of new odorous compounds produced either directly by pathogens or released by leaves or berries following infection ( Darriet et al, 2002 ; Ky et al, 2012 ; Pons et al, 2018 ; de ferron et al, 2020 ). These compounds can be linked to deleterious effects on wine quality.…”
Section: Introductionmentioning
confidence: 99%
“…The lifecycle of the most common fungal diseases is well-characterized, as is their negative impact on grapevine physiology; yet, for most diseases, the molecular mechanisms that underpin the deterioration of berry quality remain to be elucidated. Recent advances in metabolomics led to the discovery of new odorous compounds produced either directly by pathogens or released by leaves or berries following infection ( Darriet et al, 2002 ; Ky et al, 2012 ; Pons et al, 2018 ; de ferron et al, 2020 ). These compounds can be linked to deleterious effects on wine quality.…”
Section: Introductionmentioning
confidence: 99%
“…H2 hawthorn wine contained the most kinds and highest levels of lactones, which might be related to its pleasant aroma, such as caramel, coconut, and sweet . It was found that lactones could originate from raw materials or from microbial metabolism of precursors during the fermentation process . A previous study found no lactones in hawthorn berries, so it can be assumed that the lactones in H1 and H2 hawthorn wines originate from the release of precursors during fermentation.…”
Section: Resultsmentioning
confidence: 94%
“…Both compounds are associated with smoky, clove, and sweet characteristics . Previous studies have reported that volatile phenols may be extracted from oak in contact with wine during fermentation and aging . These compounds could also originate directly from the raw berries or be released from the precursor during fermentation and storage .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…γ-nonalactone has been associated with plum and cooked fruit aromas being perceived in red wines made with shrivelled berries of late maturity (Pons et al, 2008;Allamy et al, 2018). This compound is formed during alcoholic fermentation from grape-derived precursors related to the oxidation of lipids (de Ferron et al, 2020). The variations and the levels of measured γ-nonalactone concentrations were higher in 2014 and in Cabernet-Sauvignon wines compared to Shiraz wines (Table 3 and Supplementary Data Table S2 and S3).…”
Section: Evolution Of Grape and Wine Aromatic Composition According To The Sugar Accumulation Modelmentioning
confidence: 98%